2014
DOI: 10.14295/bds.2014.v17i2.991
|View full text |Cite
|
Sign up to set email alerts
|

Coronal bacterial leakage in root canals filled with single cone technique and different endodontic sealers

Abstract: <p>Objective: To evaluate coronal bacterial leakage comparing five endodontic sealers (AH Plus, Apexit Plus, Copaifera sp oil, EndoREZ and Polifil), and comparing root canals filled with EndoREZ sealer/EndoREZ® Points and EndoREZ sealer/conventional gutta-percha points.</p><p>Material and Methods: 84 human teeth were prepared and filled with gutta-percha points using the single cone technique. Roots were randomly divided into 6 groups: Apexit Plus, AH Plus, Copaifera sp oil, Polifil, EndoREZ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Resin based sealers were more resistant against bacterial microleakage. This could be attributed to flowability and dimensional stability, enhanced adaptation and better sealing ability to dentine walls (8)(9)(10). The results of this study showed that TG sealer which is resin materials was more resistant to bacterial microleakage compared with MTA Fillapex®.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Resin based sealers were more resistant against bacterial microleakage. This could be attributed to flowability and dimensional stability, enhanced adaptation and better sealing ability to dentine walls (8)(9)(10). The results of this study showed that TG sealer which is resin materials was more resistant to bacterial microleakage compared with MTA Fillapex®.…”
Section: Discussionmentioning
confidence: 79%
“…Resin-based sealers have many merits, as setting in the moisture, insoluble in tissue fluids, adequate setting time and antibacterial properties (8) . Tgadseal is an epoxy matrix resin-based root canal sealer; it is easy to mix with excellent biocompatibility (9) . Mineral Trioxide Aggregate-based root canal has been generally used for treating root perforations, pulp capping, pulpotomy, and retrograde filling.…”
Section: Introductionmentioning
confidence: 99%